Evaluation of HMF levels in unbranded flower honeys in terms of food safety - İÇLİ, Nesrin (Veterinary Journal of Ankara University, 2022)
5-hydroxymethylfurfural (HMF) is formed by reducing sugars in honey in acidic environments by the Maillard reaction and is known as a carcinogenic, mutagenic and genotoxic compound. The aim of this study is to investigate the toxic HMF content of unbranded flower honey samples sold under the sun under inappropriate conditions and unsupervised on the highway sides and to make an evaluation in terms of food safety. The quality of the analysis results was guaranteed by participating in an international proficiency test. Analysis was performed on a High-Performance Liquid Chromatography (HPLC) device with Diode Array Detector (DAD) and Refractive Index (RI) detectors- The HMF levels of 5 honey samples were determined to exceed the legal limit (40 mg kg-1). It is revealed by the current study that the honey sold on the roadside is not safe in terms of toxic HMF. In addition, 5 samples were not found to comply with the regulation in terms of glucose + fructose content and 2 samples in terms of fructose/glucose ratio. Thus, it has also been determined that these honeys are not reliable in terms of purity.
Keywords: Bee product; Veterinary Surgery; toxicity; Veteriner Cerrahi; honey; bee product; food safety; HMF; Honey; toxicity